Epidemiological Mapping of Cutaneous Leishmaniasis in Saudi Arabia: An Observational Descriptive Study - Basmah Alharbi; Mawahib Ahmed (Springer, 2024)
Abstract Cutaneous leishmaniasis (CL) is a parasitic disease that affects individuals worldwide. An epidemiological observational population-cohort study was conducted on the basis of comprehensive research on CL incidence in Saudi and non-Saudi residents. The Ministry of Health recorded the incidence of CL between January 2020 and December 2022. The chi-square test was used to analyze the data and determine CL incidence rates in age-specific incidence rates (ASIRs) and gender between Saudi and non-Saudi residents in Saudi Arabia. The study found that between 2020 and 2022, there were 2280 cases of CL in Saudi Arabia, with 1367 and 913 cases in men and women, respectively. Of Saudi nationals, 64.26% and 12.91% were male and female, respectively. The frequency of CL was higher (87.09%) among non-Saudi residents than among Saudi nationals, with a statistically significant difference (P = 0.001) between the two groups. The ASIRs for CL were higher in patients aged 15-45 years. This study revealed variations in CL incidence rates among the 13 administrative regions; Qassim, followed by Aseer, Ha'il, and Madinah, had higher rates than the other regions. These findings indicate the need for targeted interventions and public health strategies to reduce the burden on CL, particularly among non-Saudi residents.